PENGAWASAN OPERASIONAL PELABUHAN TANJUNG HARAPAN OLEH KESYAHBANDARAN DAN OTORITAS PELABUHAN KABUPATEN KEPULAUAN MERANTI - Nora Parina; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Maritime transportation is the most effective alternative in the Meranti Islands Regency because this region is an archipelago. Therefore, the need for sea transportation has a negative impact with the occurrence of disorder and the inconvenience of passengers while in port and the occurrence of traffic accidents in the territorial waters. Considering the high potential for irregularities by shipping operators, supervision is needed for the operation of the Port of Tanjung Harapan which is a port located in the capital of the Meranti Islands Regency by the KSOP of the Meranti Islands Regency. The purpose of this research is to see how the operational supervision of the Tanjung Harapan port by the KSOP class IV of the Meranti Islands Regency, as well as what factors are obstacles to the operational supervision of the Tanjung Harapan port. This type of research used in this research is qualitative with a qualitative descriptive approach and the selection of informants using a porposive sampling technique with data triangulation techniques as data analysis techniques. The results of this study found that supervision carried out by KSOP class IV of the Meranti Islands Regency still experienced a lack of human resources namely officers who conducted field supervision, inadequate port facilities to accommodate the number of potential passengers, lack of public awareness of the importance of safety when sailing with ship conditions that exceeds the capacity of the ship and does not apply strict sanctions to shipping entrepreneurs who violate the established seaworthiness standard. Keywords: Supervision, Operations, Transportation.